Layanan Konseling Kelompok : Penerapan Teknik Relaksasi Otot Progresif untuk Mengatasi Stress Belajar Siswa SLTP - Nurafifa; Ainul Fahmi; Arman Bin Anuar; Imam Pribadi (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to (1) provide an overview of how progressive muscle relaxation techniques and group counseling services affect student learning stress, (2) provide an overview of students' learning stress levels both before and after progressive muscle relaxation technique treatment, and (3) determine How progressive muscle relaxation techniques affect student learning stress. This type of quantitative research, pre-experimental with a one group pretest-posttest design approach, consisting of one treatment group. The research sample was 15 class VIII Tahfidz students who were identified as experiencing learning stress. Data collection was obtained using observation and the student learning stress scale, then analyzed using the Shapiro - Wilk test analysis which is used to test the normality of data distribution in a sample, especially in small to medium samples. The results showed that (1) students used the progressive muscle relaxation technique for learning stress in accordance with procedures that had been designed with several implementation stages, (2) the level of student learning stress before using the progressive muscle relaxation technique was high, and the level of student learning stress after using it Progressive muscle relaxation technique is low, and (3) Progressive muscle relaxation technique has the effect of helping students reduce learning stress. The results of this study indicate that the application of progressive muscle relaxation techniques can significantly reduce students' learning stress levels, providing empirical evidence that group counseling interventions are effective in improving students' psychological well-being.